Stigmatizing attitudes toward mental illness among caregivers of patients with mental disorders in China - Yuzhu Hao; Qiuxia Wu; Xuyi Wang; Yuejiao Ma; Yunfei Wang; Pu Peng; Xin Wang; Qian Yang; Yueheng Liu; Manyun Li; Li He; Qianjin Wang; et al. (Frontiers Media S.A., 2023)
ObjectiveThis study aimed to investigate stigmatizing attitudes toward depression, schizophrenia, and general anxiety disorder (GAD) among caregivers of patients with mental disorders in China.MethodsA cross-sectional study was conducted among 607 caregivers in China, using vignettes that described three mental illnesses. Data on the caregivers' attitudes and other people's attitudes toward individuals with mental disorders and their willingness to come in contact with people with mental disorders were collected.ResultsIn the three vignettes, caregivers agreed that positive outcomes outnumbered negative outcomes. The top two statements endorsing the stigma were "the person could snap out of the problem" and "people with this problem are dangerous." In the section for perceived stigma, caregivers in the GAD vignette agreed that most people believed this problem is not a real medical illness, compared to schizophrenia. The rates of the statement endorsing unpredictability were significantly different in the schizophrenia (57.2%) and depression (45.5%) vignette, in comparison to the GAD (45.6%) vignette. For personal stigma, the caregivers tended to avoid people described in the depression vignette more often than in the GAD vignette. The caregivers were most unwilling to let the person described in the vignettes marry into their family, especially in the schizophrenia vignette.ConclusionDespite the stigma and desire for social distance associated with schizophrenia, depression, and GAD, caregivers often expect positive outcomes. Actions should be taken to improve caregivers' knowledge about mental health and reduce the stigma.